Photocatalytic Dehydrogenation of Aqueous Methanol Solution by Naked and Platinized TiO2 Nanoparticles - M. Ahmed, Luma; H. Hussein, Falah; A. Mahdi, Ali (Asian Journal of Chemistry, 2012)
Nanosized titanium dioxide particles (Hombikat UV 100) doped with different percentages of platinum metal was prepared by photodeposition method. Crystallite size and photocatalytic activity was characterized by X-ray diffraction and ultraviolet-visible light spectroscopy, spontaneously. Spectrophotometer measurements have been used to determine the concentration of formed formaldehyde following Nash method at a wavelength 412 nm. Doped titanium dioxide was found more active than naked one in the existence of oxygen gas. However, naked titanium dioxide was found inactive in the existence of nitrogen gas and the suspension of aqueous methanol solution was converted to grey colour indicating the consuming of titanium dioxide lattice oxygen. The effect of loading of platinum on titanium dioxide was studied in the range 0.25-1 %. Platinized titanium dioxide with a loading of 0.5 wt % of platinum appeared to be the most active photocatalyst in the selective partial dehydrogenation of methanol. Photocatalytic dehydrogenation was made over the temperature range 278-298 K, using UVA radiation. Activation energies for formaldehyde formation were found identical on naked and platinized Hombikat (23 ± 1 kJ mol-1). The identical activation energy for the photocatalytic dehydrogenation of aqueous methanol solution over platinized and naked titanium dioxide in the presence of oxygen is believed to be associated with the transport of photoelectrons through the catalyst to the adsorbed oxygen or metal on the surface of titanium dioxide.